The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/jcm.41.5.1996-2001.2003
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the MicroSeq 500 16S Ribosomal DNA-Based Bacterial Identification System for Identification of Clinically Significant Bacterial Isolates with Ambiguous Biochemical Profiles

Abstract: Due to the inadequate automation in the amplification and sequencing procedures, the use of 16S rRNA gene sequence-based methods in clinical microbiology laboratories is largely limited to identification of strains that are difficult to identify by phenotypic methods. In this study, using conventional full-sequence 16S rRNA gene sequencing as the "gold standard," we evaluated the usefulness of the MicroSeq 500 16S ribosomal DNA (rDNA)-based bacterial identification system, which involves amplification and sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(107 citation statements)
references
References 29 publications
6
95
1
5
Order By: Relevance
“…However, despite the certain inclusion of the three stains in the Bacillus genus, not a single one could be identified at the species level, due to variations that were found in their sequences with respect to the sequences of known species. This identification difficulty is in agreement with the results reported by Woo et al (2008), who explain that this variation can occur when isolating 16S rDNA because when two different bacterial species share almost all of their 16S rDNA sequence, this technique is not able to distinguish between the two; only the genus can be determined with certainty. These results imply that these could be previously unidentified species because there is no report of their isolation in samples from the digestive tract of fish.…”
Section: Discussionsupporting
confidence: 70%
“…However, despite the certain inclusion of the three stains in the Bacillus genus, not a single one could be identified at the species level, due to variations that were found in their sequences with respect to the sequences of known species. This identification difficulty is in agreement with the results reported by Woo et al (2008), who explain that this variation can occur when isolating 16S rDNA because when two different bacterial species share almost all of their 16S rDNA sequence, this technique is not able to distinguish between the two; only the genus can be determined with certainty. These results imply that these could be previously unidentified species because there is no report of their isolation in samples from the digestive tract of fish.…”
Section: Discussionsupporting
confidence: 70%
“…With the whole genome sequencing data of more than 100 bacteria and archaea available, it has been noted that there are relatively small interoperon heterogeneities for 16S rDNAs. In our experience in 16S rDNA sequencing, both for the known species and novel genera and species, direct sequencing of the PCR products has always been successful (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). In this study, when we first amplified the 16S rDNA of HKU15 T and sequenced the PCR product directly, it was repeatedly observed that the 5' end of the PCR product could not be sequenced clearly, with the presence of multiple peaks.…”
Section: Discussionmentioning
confidence: 99%
“…In the World laboratories, it was shown that phylogenetic relationships of bacteria could be determined by comparing a stable part of the genetic code. (Woese, et al, 1985;Woo, et al, 2003). Candidates for this genetic area in bacteria included the genes that code for the 5S, the 16S and the 23S rRNA and the spaces between these genes.…”
Section: Introductionmentioning
confidence: 99%